First Report of Macrophomina euphorbiicola Causing Charcoal Rot of Stevia in Paraguay - Sanabria-Velazquez, Andres (Plant disease, 2022)
Stevia (Stevia rebaudiana [Bertoni] Bertoni) is a perennial plant originating in Paraguay. Stevia is primarily cultivated for the production of non-caloric sweeteners. In December 2018, wilted stevia cv. 'PC4' were recovered from two separate fields of 0.3 ha (24.66 S 56.46 W) and 0.5 ha (24.69 S 56.44 W), both with 3 years history of stevia production in San Estanislao County, San Pedro, Paraguay. The wilted plants were randomly distributed in beds covered with plastic mulch and a 30% disease incidence was recorded. Dark brown septate hyphae and microsclerotia were observed on stem bases and black necrotic roots of the wilted plants. Root and crown regions were washed, cut into 0.5 to 1.0 cm pieces, and then surface-disinfested with 0.6% NaOCl before placing them in Petri dishes containing acidified potato-dextrose-agar. Plates were incubated for one week at 25 ± 5°C under fluorescent light with a 12 h photoperiod yielding five isolates SP1PY, SP2PY, SP3PY, SP4PY and SP5PY with gray-black colonies without conidia but showing numerous microsclerotia. Twenty microsclerotia from pure cultures of five isolates were measured, with mean width 38.8 ± 4.7 µm and length 68.8 ± 15.5 µm. Fungal DNA was extracted from mycelia of five isolates for PCR amplification of the internal transcribed spacer (ITS) and translation elongation factor 1-alpha (TEF1-α) using ITS4/ITS5 and EF1-728F/EF-2 primers (Machado et al. 2019). The resultant amplicons were sequenced at Eton Bioscience (Research Triangle Park, NC) and deposited in the NCBI GenBank database (ITS: MT645815, OM956150, OM956151, OM956152, OM956153; and TEF1-α: MT659121, OM959505, OM959506, OM959507, OM959508). Sequences were aligned with several isolates of Macrophomina spp. previously reported (Huda-Shakirah et al. 2019; Machado et al. 2019; Santos et al. 2020; Poudel et al. 2021) using ClustalW. Alignments (ITS and TEF-1α) were concatenated to generate a maximum likelihood tree using MEGA7. The novel isolates grouped into the M. euphorbiicola clade with 95% of bootstrap support. Stevia plants cv. 'Katupyry' were grown in 10 cm-diameter nursery bags containing autoclaved sandy soil and kept under greenhouse conditions (28 ± 5°C; 16 h photoperiod). Fifteen plants per isolate (n=75) were inoculated by adding 20 g of rice infested with M. euphorbiicola to each plant. Infested grains were distributed around the crown of the plant at a depth of 0.5 cm; non-infested rice was added to four control plants. Lower-stem lesions and microsclerotia of M. euphorbiicola developed on all inoculated plants. No lesions or microsclerotia were observed on control plants. The M. euphoribiicola fungus was re-isolated from inoculated stevia plants but not from the non-infested rice treated plants. Koch's postulates were repeated twice with similar results. Previously, M. phaseolina was reported causing charcoal rot on stevia in Egypt (Hilal and Baiuomy 2000), and in North Carolina, USA (Koehler and Shew 2017). However, Paraguayan isolates grouped with isolates of M. euphorbiicola based on the combined sequences of the ITS and TEF-1α regions. Machado et al. (2019) reported M. euphorbiicola causing charcoal rot on castor bean (Ricinus communis) and bellyache bush (Jatropha gossypifolia) in Brazil, which borders northeast Paraguay, a major stevia production area. This pathogen has a significant impact on stevia production during hot, dry weather by reducing the number of harvestable plants and increasing replanting costs in perennial production systems